Application of X-ray technique in nondestructive evaluation of eucalypt wood - Tomazello, M.; Brazolin, S.; Chagas, M. P.; Oliveira, J. T. S.; Ballarin, Adriano Wagner [UNESP]; Benjamin, C. A. [UNESP] (Univ Bio-bio, 2008)
X-rays were initially used for the inspection of special-purpose wood pieces for quantitative evaluation properties of different species. X-ray densitometry has had its use expanded ill dendroclimatology of Picea engelmannii trees. Subsequent laboratories developed applications of X-ray densitometry for environmental, wood science and technology, and related areas. This paper describes the basic methodology of X-ray densitometry applied to the eucalypt wood analysis, as well its presenting the results of applications in three areas: (i) evaluation of wood biodegradation by white rot fungi, (ii) detection of sapwood and heartwood, and (iii) determination of the effect of management oil wood properties. The wood decayed by white rot fungi was detected by X-ray densitometry with it decreasing wood density due to the biodegradation of cell wall components. The sapwood and heartwood of eucalypts were separated in response to the attenuation of X-rays, reflected by the wood anatomical structure and chemical composition. Also, Ill eucalypt trees after the application of irrigation and i characteristic wood density profiles were detected. Ill addition, the significant potential of X-ray densitometry for eucalypt wood research and analysis is discussed.
Keywords: eucalypts; X-ray densitometry; sapwood; heartwood; density; white rot fungi